Insight into characteristics in rice starch under heat- moisture treatment: Focus on the structure of amylose/amylopectin - Weijie Qi; Siying Kong; Xiaoqiang Li; Zeyu Peng; Lina Sun; Zhaohua Wang; Jianjun Cheng (Food Chemistry: X)
Heat-moisture treatment (HMT) could improve the structure and physicochemical characteristics of rice starch, the structural changes of amylose and amylopectin needed to be further investigated. Hence, the starch, amylose and amylopectin were modified by HMT with different moisture contents (MC). As MC increased, starch granules became irregular, amylose appeared molten while amylopectin was less damaged. The crystal structure of starch was disrupted by HMT. The increase in the double helix structure of amylose exhibited more drastic tendency towards molecular rearrangement than amylopectin did. In addition, the reduced proportion of amylopectin A chain could affect the rearrangement of amylose. The solubility and pasting temperature improved, but the enthalpy decreased. Moderate MC (20 %, 25 %) could enhance the viscosity and dynamic viscoelasticity. HMT promoted the conversion of RDS to RS, which was significantly increased by 85.26 % at HMT-40 %. These findings contributed to a better understanding of the mechanisms by which HMT affected starch.